2017
DOI: 10.1002/1873-3468.12708
|View full text |Cite
|
Sign up to set email alerts
|

Peptide microarray analysis of the cross‐talk between O‐GlcNAcylation and tyrosine phosphorylation

Abstract: O-GlcNAcylation of proteins regulates important cellular processes. A few reports noted that O-GlcNAcylation exhibits cross-talk with tyrosine phosphorylation. With an activity-based microarray analysis of 256 tyrosine kinase peptide substrates, we found that phosphorylation of six peptides by Jak2 inhibits their subsequent O-GlcNAcylation. However, O-GlcNAcylation has no detectable effect on their subsequent phosphorylation. A specific peptide (ZO3_357_371), derived from the ZO-3 protein, was studied in detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…A recent study has shown that STAT3 is O-GlcNAcylated on T717, implying the interplay with phosphorylation to regulate STAT3 activity [94]. Moreover, the cross-talk between OGN and Jak2-mediated tyrosine phosphorylation has been detected in the peptide microarray assay for OGT and tyrosine kinase [95]. The findings implicate that O-GlcNAc is an activator of the cilia-mediated leptin-LepR-JAK2-STAT3 pathway in the hypothalamus.…”
Section: O-glcnac Regulates Energy Homeostasis In the Hypothalamusmentioning
confidence: 79%
“…A recent study has shown that STAT3 is O-GlcNAcylated on T717, implying the interplay with phosphorylation to regulate STAT3 activity [94]. Moreover, the cross-talk between OGN and Jak2-mediated tyrosine phosphorylation has been detected in the peptide microarray assay for OGT and tyrosine kinase [95]. The findings implicate that O-GlcNAc is an activator of the cilia-mediated leptin-LepR-JAK2-STAT3 pathway in the hypothalamus.…”
Section: O-glcnac Regulates Energy Homeostasis In the Hypothalamusmentioning
confidence: 79%
“…Also in NF-jB signaling, p65 is O-GlcNAcylated at Thr305 and Ser319, where phosphorylation at Thr308 may prevent O-GlcNAcylation at Thr305 [100]. In addition, crosstalk was hypothesized to also occur between tyrosine phosphorylation and O-GlcNAcylation [101], which sites were later validated using a peptide microarray screening study by Pieters and coworkers [102]. One specific example occurs on STAT5, where O-GlcNAcylation of STAT5 controls tyrosine phosphorylation [103].…”
Section: Phosphorylation/o-glcnacylation Crosstalk At the Substrate Lmentioning
confidence: 99%
“…For example, O-GlcNAcylation of p53 at Ser149 hampers phosphorylation at Thr155, a site targeted by the COP9 signalosome, finally resulting in p53 ubiquitination and degradation [99]. In addition, crosstalk was hypothesized to also occur between tyrosine phosphorylation and O-GlcNAcylation [101], which sites were later validated using a peptide microarray screening study by Pieters and coworkers [102]. For example, in the circadian clock, O-GlcNAcylation of the period circadian regulator 2 (PER2) at Ser662 in its regulatory region blocks casein kinase I-dependent PER2 phosphorylation [82].…”
Section: Phosphorylation/o-glcnacylation Crosstalk At the Substrate Lmentioning
confidence: 99%
“…Another specific substrate peptide was identified among tyrosine kinase substrates and was derived from the tight junction ZO-3 protein: ZO-3_357-371. 23 Again replacing the serine at the modification site with an alanine yielded an OGT inhibitor. To identify the minimum structural requirements for OGT inhibition, two series of shorter peptides based on the original sequences were synthesized and they were tested as OGT inhibitors (Fig.…”
mentioning
confidence: 99%